The Nature and Function of the Ancient Turkic Functional Word “Birlan” in Modern Turkic Languages (Using the Example of the Kazakh Language) - Zhunussova, Bayan; Baimurynov, Zhanbolat; Kenzhegaliyev, Sayan; Sametova, Zhanakul; Kenzhebekova, Aigerim; Merey Balabekova (Forum for Linguistic Studies, 2024)
It is known that Soviet Turkologists believe that the affix of the instrumental suffix exists only in the Kazakh language among Turkic-speaking peoples. Because in the modern Kazakh language, “birlan”, which is the archetype of the form “men”, which was once a case affix, once a conjunctional functional word, was not an affix of the case category, but a particle functional word. Also, when developing the theory of grammar of the Turkic peoples of Central Asia, linguists of the national republics were guided by the grammatical theory of the Russian language. And in the grammar of the Russian language, the number of declensions is six. For such reasons, in most modern Turkic peoples, only six types of the category of declension are indicated. The article shows the forms formed by the mosaic method in modern Turkic languages from the early particle “birlan”, some of which are used as affixes, that is, the affixes of the instrumental case exist not only in Kazakh, but also in other Turkic languages. The modern Kazakh version of the former particle “birlan” is “men”. The grammatical function of this form in the modern Kazakh language is very large: despite the change in form, it has retained its original meaning, as well as many functions that have been added later. However, the semantic motivation between the conjunction and conjunctive is observed, and nevertheless the two are developing separately as two different grammatical categories.